Amino acid composition, and determination and prediction of the protein digestibility of different sugarcane yeasts in broilers - Barbosa, Emanuela Nataly; Rabello, Carlos; Lopes, Claudia; Silva, Edney; Freitas, Ednardo (Revista Ciência Agronômica, 2018)
The aim of this study was to determine the amino acid composition and digestible protein values of different sugarcane yeasts, as well as to generate prediction equations for the apparent digestibility coefficient of dry matter (ADCDM) and crude protein (ADCCP), based on the chemical composition of the yeast and the age of the broilers. Four ileal digestion trials were carried out with 690 broilers, divided into the pre-starter, starter, growth and final phases. The birds were housed in metabolic cages and distributed in a completely randomised design, consisting of five treatments and six replications of eight, six, five and four birds respectively in each experimental phase. The treatments consisted of one reference feed and four test feeds, substituting 30% of the reference feed with four different yeasts. Yeasts two and four showed a higher percentage of amino acids. However, yeast two had the highest percentages of ADCDM, ADCCP and digestible protein: 83.64, 81.22 and 14.66% in the pre-starter phase; 78.09, 78.28 and 14.13% in the starter phase; 76.74, 74.75 and 13.49% in the growth phase; and 72.98, 71.21 and 12.85% in the final phase respectively. There was an average reduction of 0.424% in ADCDM and 0.428% in ADCCP for each day the birds aged. The following prediction equations were generated from the composition of the yeasts and age of the chickens: ADCDM = 77.4 - 0.424*(age) - 7.51*(DM) - 45.01*(EE) and - 0.424*(age) + 3.02*(CP) + 126.93*(EE) - 0.03*(GMD) and ADCCP = 606.9-0.428*(age) -5.8*(DM) - 0.01*(GMD) and -0.426*(age) + 2.68(CP) + 139.7*(EE) - 0.03*(GMD).